Rubber Nanocomposites for Extreme Environments: Critics and Counterintuitive Solutions - Valentini, Luca; Lopez-Manchado, Miguel Angel (Frontiers in Materials, 2018)
Elastomers are commonly considered the workhorses of the industrial and automotive components because of their good mechanical properties, their good resistance to lubricants and greases and their relatively low cost. Nowadays, there is a need to develop high performance elastomeric materials in extreme environments; for example there is and will continue to be, a need to develop high performance elastomeric sealing materials for oil and gas operational drilling applications in extreme locations where also the extreme conditions such icing problems become hazardous, limiting the extraction activities unless reliable solutions are found as well as in transportation where bearing seals mounted on aircraft components are subjected to icing problems that require a solution. All these applications will require the exploitation of new and novel polymers and new and novel reinforcement systems. Carbon nanotubes (CNTs) are being evaluated and are in some use today, but graphene nanoplatelets (GNPs) and its many derivatives offer an opportunity to develop novel high performance materials crucial to nowadays and future industrial applications. In a growing fields of applications such elastomeric nanocomposites target the permeability reduction to prevent blistering, the reduction of the stress cracking and the capability to retain tensile strength at high temperature and pressure. This perspective will address this need by indicating new multifunctional elastomeric nanocomposites (elastomer plus carbon nanotubes and graphite nanoplatelets) combined with superior barrier and mechanical properties.